Adsorption of Malachite Green Dye from Liquid Phase Using Hydrophilic Thiourea-Modified Poly(acrylonitrile-co-acrylic acid): Kinetic and Isotherm Studies - Abel A. Adeyi; Siti N. A. M. Jamil; Luqman C. Abdullah; Thomas S. Y. Choong (Journal of Chemistry, 2019)
Thiourea-modified poly(acrylonitrile-co-acrylic acid) (TU-poly(AN-co-AA)) adsorbent was a surface modification of poly(acrylonitrile-co-acrylic acid) synthesized by facile redox polymerization. Surface functionalization with thiourea was carried out to provide hydrophilicity on the surface of a polymeric adsorbent. Fourier transform infrared (FTIR) spectrometer, scanning electron microscope (SEM), and Zetasizer characterized the morphology and structures of TU-poly(AN-co-AA). Copolymerization of poly(acrylonitrile-co-acrylic acid) and its successful incorporation of the thioamide group was confirmed by the FTIR spectra. The SEM micrographs depicted uniform and porous surface morphologies of polymeric particles. The average diameter of modified and unmodified poly(acrylonitrile-co-acrylic acid) was 289 nm and 279 nm, respectively. Zeta potentials of TU-poly(AN-co-AA) revealed the negatively charged surface of the prepared polymer. Adsorption capacities of hydrophilic TU-poly(AN-co-AA) were investigated using malachite green (MG) as an adsorbate by varying experimental conditions (pH, initial concentration, and temperature). Results showed that the pseudo-second-order reaction model best described the adsorption process with chemisorption being the rate-limiting step. Furthermore, Elovich and intraparticle diffusions play a significant role in adsorption kinetics. The equilibrium isotherm has its fitness in the following order: Freundlich model > Temkin model > Langmuir model. Thermodynamic analysis indicates that the sorption process is spontaneous and exothermic in nature. The reusability results suggested potential applications of the TU-poly(AN-co-AA) polymer in adsorption and separation of cationic malachite green dye from wastewater.